Health care professionals' knowledge and attitudes toward telemedicine - Muhammad Salman Bashir; Diana Selvamony Lalithabai; Shahad AlOtaiby; Amani Abu-Shaheen (Frontiers Media S.A., 2023)
BackgroundThe utilization of modern communication technology in the healthcare field is known as telemedicine, and it represents an advancement in the healthcare industry. For effective implementation of these technologies, healthcare professionals must possess the appropriate knowledge and hold a positive perspective toward the implementation of telemedicine. The current study aims to evaluate the knowledge and perspective of healthcare professionals in King Fahad Medical City, Saudi Arabia toward telemedicine.MethodsThis study was carried out in a diverse hospital, King Fahad Medical City, Saudi Arabia and it was a cross-sectional study. The study took place from June 2019 until February 2020, during which 370 healthcare professionals, including physicians, nurses, and other healthcare professionals participated. The data was gathered by using a structured self-administered questionnaire.ResultsThe analysis of the data revealed that the majority of the healthcare professionals who participated in the study, 237 (63.7%), had limited knowledge of telemedicine. About 41 (11%) participants had a good understanding of the technology, and 94 participants (25.3%) had extensive knowledge. The overall attitude of the participants toward telemedicine was positive, with a mean score of 3.26. The mean attitude scores varied significantly (P < 0.001) among the different professions, with physicians scoring 3.69, allied healthcare professionals scoring 3.31, and nurses scoring 3.07. The coefficient of determination (R2) was used to evaluate the variation in attitude toward telemedicine and it was found that education (12.4%) and nationality (4.7%) had the least impact on the attitude toward telemedicine.ConclusionHealthcare professionals are crucial to the successful implementation and continuity of telemedicine. However, despite their positive attitude toward telemedicine, most of the healthcare professionals who participated in the study had limited knowledge of it. There were differences in attitude among different groups of healthcare professionals. As a result, it is necessary to create specialized educational programs for healthcare professionals to guarantee the proper implementation and continuation of telemedicine.